Relation between the curricular execution and the teaching performance - Garcia-Conislla, Maria V. (2020)
The present research tried to demonstrate how the curricular execution is related to the teaching performance regarding the fulfillment of what is programmed in the respective university syllables and in the different thematic areas according to a schedule, methodology, materials and evaluation. The methodology used is to basic type, non-experimental design of hypothesis contrast level, descriptive - correlational, because a relationship is established between the variables of Curriculum Execution and Teaching Performance, according to the perspective of the students of the Faculty of Education. The technique used was the survey. The sample consisted of 80 students; the sampling was carried out by random selection. The results were, p = 0.000. So there is enough statistical evidence to reject H0. Consequently, it was shown that there is a relationship between the variables and not random. Therefore, it is concluded that there is a significant relationship between curriculum execution and teaching performance, according to university vocational training students. (r = 0.895 and p = 0.000); it is important because the better the curriculum execution, the better the teaching performance.